Diseño de un circuito de actividades de turismo alternativo en el cantón La Maná, provincia de Cotopaxi, 2015 - Hurtado Meza, Wagner Argenis (2016)
Tourism is an industry that is constantly changing and increasingly points to the realization of sustainable or alternative therefore tourism is involved in direct contact with nature and cultural expressions around him with an attitude and commitment to meet, respect, enjoy and participate in the conservation of natural and cultural resources. In this thesis it will be announced the different activities that can be developed through alternative tourism focused more on the design of a circuit of activities of adventure tourism in the Canton La Mana, which has been little explored despite all this place provides powers for the implementation of various tourism activities.